The Effectiveness of Communication Media in Supporting Fagogoru Philosophy-Based Communication Strategies in the Implementation of Education Policies (Case Study of the Central Halmahera Regency Education Office) - Nur Rahmawati Lie; Novianty Elizabeth Ayuna; Umar S. Bakry (International Journal of Technology and Education Research, 2025)
The implementation of education policy requires the necessity of using effective communication strategies so that policy messages can be well received by the public. Especially if the implementation of the policy is in areas that are still experiencing development transitions from various aspects. This study aims to analyze the effectiveness of communication media in supporting communication strategies based on the philosophy of fagogoru in the implementation of education policies in Central Halmahera Regency. The method used is a qualitative approach with explanatory case studies. Data were obtained through interviews, observations, documentation, and online questionnaires involving service providers and service recipients with a total of 18 informants. The results of the study show that the communication media used, such as correspondence, WhatsApp, Zoom Meeting, and social media, are relatively effective in reaching the community even though there are still obstacles in the form of delays in information distribution, limited digital literacy, lack of individual awareness, and uneven infrastructure. The integration of this fagogoru philosophy with the values of Ngaku re Rasai, Budi re Bahasa, Sopan re Respect, and Mtat re Memoy strengthens the communication strategy so that it is more inclusive, polite, and harmonious. The combination of modern communication media and local cultural values has been proven to increase the effectiveness of education policy implementation by increasing public understanding, participation, and trust in the implementation of education policies.